Predators of the sea urchin Diadema mexicanum (Diadematoida: Diadematidae) at the Eastern Tropical Pacific coral reefs - Hernández Pérez, José Carlos (2024)
Introduction: The coral reefs of Isla del Coco National Park are some of the most pristine ecosystems on Earth. The sea urchin Diadema mexicanum (Diadematoida: Diadematidae) is a common inhabitant with a pivotal role in the ecology of this unique ecosystem. Objective: In this study, we identified the predominant predators of D. mexicanum and estimated the predatory consumption rates. We also determined predation rates at different sea urchin sizes and at sites with contrasting refuge availability. Methods: We use field video recording observations and tethering experiments. Results: The balistid Sufflamen verres and the labrid Bodianus diplotaenia were identified as predators of small and medium size D. mexicanum; the labrids Thalassoma grammaticum and B. diplotaenia (juvenile) and the tetraodontid Arothron meleagris were attempted predators; and Canthigaster punctatissima and Holacanthus passer were scavengers. Larger sea urchins (> 30 mm) were also preyed upon during the tethering experiments. Furthermore, a clear effect of the site on survival of the different sea urchins’ sizes was noted. No difference in the sea urchin predator biomass was found among sites, which highlights the importance of site complexity on survival. At high and medium complexity sites, large individuals had better survival, while at the low complexity site, there was almost no differences in survival rates among the three size classes. Our results also show that a high abundance of these predatory fishes, above 0.04 ind m-2, guarantees a low sea urchin density. Below this threshold, a higher variability in sea urchin density is observed Despite not being registered with the video recordings, lobsters were observed once preying upon a large sea urchin individual. Conclusions: This study identifies a keystone fish guild with high predation rate for Diadema in the National Park, which suggests that protective actions have positively benefited predatory fish and lobster populations.